Pencarian Nasabah dengan Menggunakan Data Mining dan Algoritma C4.5 Koperasi MADUMA Subang - Timbo Faritcan Siallagan (Maranatha University Press, 2015)
Abstract - Credit is the provision of money or bills that can be equated with it, based on consent or agreement between the bank and the borrowing other party require that borrowers pay off its debt after a certain period of time by the giving of flowers. Although the Lender has approved a credit proposed by the debtor, but the credit analysis to be done of debtors who have been approved so that the cause of non-performing loans can be examined and get a good classification for the determination of the appropriateness of granting credit. In granting credit need to analyse the needs of creditors, then that must be known in advance is the principles that need to be ditegakan in the framework of granting credit. Things that need to be considered in granting credit to customers is the principle 6 C's Analysis. With these problems, then there is need for troubleshooting existing solutions, by making a decision support System. Thus this decision support System will be able to meet the expectations to be achieved. The algorithm C 4.5 is algorithms used to create the decision tree. Decision tree classification method and prediction is a very powerful and famous. Getting rich in information or knowledge that is conceived by training data, the accuracy of the decision tree will be increased.Keywords - credit Analysis, principles 6 C's Analysis, Data Mining and algorithms C4.5